Prevalence and Risk Factors of Gastroesophageal Reflux Disease Among Medical and Dental Students of Rawalpindi/Islamabad - Shahzad, Asima; Mashhadi, Syed Fawad; Shahid, Mehreen; Khalid, Sumaira; Rehman, Ata Ur; Mukhtar, Ashan; Ahmed, Ishraq (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To determine the prevalence of gastroesophageal reflux disease among medical and dental students of Rawalpindi Islamabad Pakistan and to find the associated risk factors. Study Design: Analytical cross-sectional study. Place and Duration of Study: Students of Medical colleges in Rawalpindi Islamabad Pakistan, from March to May 2021. Methodology: Non-probability convenience sampling technique was used. Sample size was found to be 352 using Rao soft.Only undergraduate students from Rawalpindi Islamabad Pakistan were included whereas postgraduate students were excluded. The data was collected via online distributed google forms and analyzed by SPSS version 25.0. Results: There were 157(44.6%) males and 195(55.41%) females among whom 296(84.1%) were enrolled in medical program and 56(15.9%) in dental program. 94 students (26.7%) reported having symptoms of gastroesophageal reflux disease .Based on a GERD score of >=4, 35(9.94%) students were diagnosed with gastroesophageal reflux disease .Use of analgesics (OR=3.11[95% CI 1.32-7.36]; P≤0.010), family history of gastroesophageal reflux disease (OR=6.48[95% CI 3.09-13.57]; P≤0.000),family history of peptic ulcer (OR=2.85[95%CI 1.18-6.83] P≤0.038), frequent use of non-steroidal anti-inflammatory drugs(P≤0.013) had a significant association with the presence of gastroesophageal reflux disease . Conclusion: Gastroesophageal reflux disease was diagnosed in approximately 10% of students. There was a significant association of Gastroesophageal reflux disease with use and frequent consumption of non-steroidal anti-inflammatory drugs and family history of peptic ulcer/Gastroesophageal reflux disease